1999
DOI: 10.1002/(sici)1097-4652(199909)180:3<431::aid-jcp14>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of prostate cancer cell division by glucose

Abstract: Previous studies have shown that rapid cell proliferation is associated with elevated glucose consumption. However, those studies did not establish whether glucose is required for prostate cancer cell proliferation or define the molecular mechanisms by which glucose regulates cell division. We addressed these issues by studying two metastatic human prostate cancer cell lines: DU145, which is androgen independent and highly proliferative; and LNCaP, which is androgen dependent and relatively slow growing. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 35 publications
6
24
1
Order By: Relevance
“…These findings support previous studies, showing 2DG-induced growth inhibition and cytotoxicity in MDA-MB231 cells [32], and FaDu cells [34], accompanied by increases in parameters indicative of oxidative stress and these effects were enhanced with BSO treatment. Furthermore, our results were consistent with a previous study by Singh et al (1999) showing that the growth rate of rapidly dividing DU145 prostate cancer cells depend on high levels of glucose consumption, whereas the growth rate of relatively slow-growing LNCaP cells are much less dependent on glucose [35]. They found a direct correlation between glycolytic capacity and degree of growth inhibition in response to glucose deprivation for these two cell lines.…”
Section: Discussionsupporting
confidence: 94%
“…These findings support previous studies, showing 2DG-induced growth inhibition and cytotoxicity in MDA-MB231 cells [32], and FaDu cells [34], accompanied by increases in parameters indicative of oxidative stress and these effects were enhanced with BSO treatment. Furthermore, our results were consistent with a previous study by Singh et al (1999) showing that the growth rate of rapidly dividing DU145 prostate cancer cells depend on high levels of glucose consumption, whereas the growth rate of relatively slow-growing LNCaP cells are much less dependent on glucose [35]. They found a direct correlation between glycolytic capacity and degree of growth inhibition in response to glucose deprivation for these two cell lines.…”
Section: Discussionsupporting
confidence: 94%
“…These findings support previous studies, showing 2DG-induced growth inhibition and cytotoxicity on MDA-MB231 cells (Andringa et al, 2006), and on FaDu cells (Simons et al, 2007). Furthermore, our results were consistent with a previous study by Singh et al (Singh et al, 1999), showing that the growth rate of rapidly dividing DU145 prostate cancer cells depend on high levels of glucose consumption, whereas the growth rate of relatively slow-growing LNCaP cells are much less dependent on glucose (Singh et al, 1999). They found a direct correlation between glycolytic capacity and degree of growth inhibition in response to glucose deprivation for the cell lines.…”
Section: Discussionsupporting
confidence: 78%
“…10 In vitro study also suggested that glucose may not be required for androgen-dependent prostate cancer cells because LNCaP cells can grow at control rates even in the presence of only 0.05 g/l glucose. 11 As rapid cell proliferation in malignant tumors is associated with increased energy supply, if glucose consumption is not elevated in prostate cancer, alterative metabolic approach, especially fatty acid oxidation may exist dominantly to provide bioenergy for abnormal cells proliferation and growth.…”
Section: Introductionsupporting
confidence: 77%